Cross-validation of the Persian Version of the Revised Scale of Prolonged Grief Disorder - Rahim Yousefi; Armin Haghnazari Esfahlam (روانشناسی بالینی و شخصیت)
Introduction: Prolonged Grief Disorder is a newly established diagnostic category included in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders. The present study aimed to introduce and psychometrically validate the Persian version of the Revised Prolonged Grief Scale.Method: The study employs a descriptive-survey design. For this purpose, 400 undergraduate students from Shahid Madani University of Azerbaijan were selected through purposive sampling and assessed using the Persian version of the Revised Prolonged Grief Scale and the Grief Experience Questionnaire.Results: Exploratory factor analysis indicated that a general factor can be extracted, accounting for 52% of the total variance in the scores. Confirmatory factor analysis demonstrated that the extracted single factor exhibits a good fit. The item homogeneity coefficient was 0.89 when calculated using Cronbach's alpha and 0.88 when determined through the split-half method. The positive and significant correlation coefficient between the scores of prolonged grief disorder and the experience of grief indicates the convergent validity of the prolonged grief disorder scale. The diagnostic validity of the Prolonged Grief Disorder Scale was confirmed by comparing two groups: subjects diagnosed with prolonged grief disorder and their normal counterparts, revealing a significant difference between the two groups.Discussion and Conclusion: The Persian version of the Prolonged Grief Disorder Scale demonstrates adequate validity for the local sample and can be utilized as a reliable and effective tool for both clinical and research purposes.